Produção de conhecimento feministas em universidades brasileiras - Oliveira, Elismênnia Aparecida (2015)
In this thesis is discussed and examined the introducing of the feminist production of knowledge in Brazilian University. I am concerned about the challenges, frequency and feminist influences in universities. I achieved, by a qualitative methodology, a reflective research based on possible ways to study the issue which, after a laborious path, led up to the use of three procedures: 1 ) the analysis of the study group leaders programs and research centers found on the Diretório de Grupos e Núcleos CNPq research centers, taking into account the registered groups; 2) the arrangement and analysis of Brazilian feminist literary production concerning to the introduction of feminism in the universities of the country; 3) the analysis of interviews with leaders of seven research centers already scanned. Taking into account the methods, the analyzes were conducted from contemporary social theory, with emphasis on: the feminist theory and epistemology, especially: post-structuralist, including the production of the ‘Third World’ feminists and post and decolonial thought and Subaltern Studies Group and post-structuralism. The union of these options are discussed issues concerning the creation of universities and access to them by the rise of feminism in Brazilian universities. The analysis points out the influences of the permanence of the colonization process, still in force and the consequence that, among others, is the invisibility of feminist knowledge production in Brazilian universities. Also, this process exhibit the difficulty of the rise of both women researchers in general and feminist researchers in particular until the most prestigious positions in various areas of science, this event occurs in Brazil and other countries. Finally, the research shows that there is a homogenization in the production of knowledge which hinders the spread of new looks and new epistemologies.